PEMANFAATAN MINYAK WORTEL YANG RAMAH LINGKUNGAN SEBAGAI PENGGANTI XYLOL DALAM PROSES DEPARAFINISASI - indah sari (IKesT Muhammadiyah Palembang, 2024)
Introduction: hematoxylin Eosin is a common dye used in histology laboratory examination. One of the stages of hematoxylin staining of eosin is the process of deparafinization. Deparafinisasi is a process to remove or dissolve paraffin from tissue and perform a clearing process before being observed under a microscope so that maximum color absorption at the time of tissue staining and look clear. The deparafinisai process is usually done by using xylol to dissolve paraffin in the form of fat. Xylol is commonly used as an ingredient for clearing and deparafinization processes. Continuous use of xylol can cause toxicity to the body and health. Medical laboratory workers, especially histology officers in charge of tissue coloring have a dangerous risk of chemical, biological, mechanical and environmental hazards so that a safer and cheaper alternative to xylol is needed. Alternative use of xylol is done to minimize harm to health and the environment, among others, by finding a substitute for xylol. Some natural ingredients such as carrot oil, pine oil, rose oil and olive oil can be used instead of xylol. Carrots relatively do not contain sulfur elements, so they do not cause air pollution, and can also improve the efficiency of agricultural resource utilization. Purpose of the study: to utilize environmentally friendly carrot oil as a substitute for xylol in the deparafinization process. Method: the research design used is true experiment design. Samples of human breast tissue (mammae) to see the results of the examination using an alternative reagent carrot oil and xylol as a control. The examination data will be processed by descriptive analysis based on the results of the assessment score of tissue preparation. Result: hematoxylin eosin staining using xylol get very good results of 100% while using carrot oil get very good results of 87.5% in the process of deparafinization. Discussion: Carrot oil can be used as a substitute for xylol in the process of deparafinization.